Molecular Targeted Therapies for Rhabdomyosarcoma: Focus on Hedgehog and Apoptosis Signaling - Fulda, S. (Klinische Pädiatrie, 2013)
Dysfunction of cell death and proliferation pathways can contribute to rhabdomyosarcomagenesis, tumor progression and treatment resistance. Therefore, the identification of key signaling hubs and molecules that govern the decision between life and death of a cancer cell is expected to open new perspectives for drug discovery. For example, programmed cell death pathways can be engaged in rhabdomyosarcoma (RMS) cells by recombinant soluble proteins, monoclonal antibodies or small-molecule inhibitors. In addition, the hedgehog (Hh) cascade is often aberrantly activated in RMS and represents a promising target for therapeutic intervention. The development of molecular targeted cancer therapeutics will likely lead to more effective treatment options for patients with RMS.
Keywords: rhabdomyosarcoma; apoptosis; TRAIL; Bcl-2; hedgehog